Integrasi Nilai-Nilai Moderasi Beragama pada Pembelajaran Pendidikan Agama Islam (PAI) di SD Islam Al Azhar 11 Surabaya - Zakkyfanani, Ahmad; Khoiroh, Haniatul (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
This research aims to describe the integration of moderate religious values in the learning of Islamic Education (PAI) at Al Azhar 11 Islamic Elementary School in Surabaya. The method used is descriptive qualitative research with an observational, interview, and documentation approach. The research results show that PAI teachers play a strategic role in designing, implementing, and evaluating learning that contains moderate values such as tasamuh (tolerance), i'tidal (justice), tawazun (balance), and tawassuth (middle path). The effectiveness of integrating these values is supported by a flexible curriculum, adequate learning facilities, and institutional support. However, limitations in time, a lack of technical guidance from the government, and insufficient contextual learning resources pose obstacles to its implementation. In conclusion, PAI learning that integrates moderation values has the potential to shape students' inclusive and tolerant character, but it needs to be supported by adequate policies and resources for optimal learning outcomes.